The Institutionalization of Political Risk Assessment by Chinese Multinational Firms - Alon, Ilan; Jiménez, Alfredo; Liu, Hui; Wang, Hua (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
Some researchers have claimed that Chinese firms are impervious to political risk, calling into question the institutionalization of political risk by Chinese firms. Building on resource dependence theory and the literature on non-market strategies, this study finds significant impact by ownership structure, firm scale, and the degree of internationalization on the institutionalization of political risk assessments (IPRA) by Chinese firms. As such, state-owned firms and larger firms cultivate a higher level of IPRA. We find a positive impact of a firm’s scale and scope of internationalization, but insignificant impact of depth of internationalization.